The Role of Schools in Improving Abilities Disaster Preparedness: Nursing Perspective - Muhammad, Al Azhar; Suni, Arsad; Murwidi, Imam Cahyo; Sudrajat, Ace (Poltekkes Kemenkes Palu, 2023)
Earthquake disasters can occur at any time and humans are not yet able to detect when they can occur. Children are included in a group that is vulnerable to the impact of disasters because of their lack of knowledge regarding disaster mitigation. To minimize the impact of disaster events, education on disaster mitigation is needed. To determine the influence of the school's role in increasing students' disaster preparedness abilities in junior high schools in Ternate City. Quasi-experimental research type with a one-group pre-post test design. Data were analyzed using the non-parametric Wilcoxon signed-rank test. The research subjects consisted of teachers (seven respondents) and students (90 respondents). The data were processed using the non-parametric Wilcoxon signed-rank test. The analysis results showed that asymp. sign. (2-tailed) The teacher's score is 0.018 and the student's score is 0.000, where the value of 0.000 is smaller than p value = 0.05, so it can be concluded that there is an increase in disaster preparedness abilities among schoolteachers and students. The role of schools is very important in disseminating disaster mitigation education as basic knowledge that requires learning as early as possible, so that a culture of disaster mitigation grows both before, during, and after a disaster. There was an increase in the ability of teachers and students at school after a disaster preparedness simulation was carried out at a junior high school in Ternate City.